Formulação e caracterização de doces cremosos a base de frutas nativas e adicionados farinha de sementes de pinhão - Abreu, Gabriele Avozani (2024)
Agricultural advances have replaced native species with monocultures, posing a significant threat to biodiversity and sustainable development. Given the promising prospects exploting of native species, studies have sought to use fruits such as guabiroba and uvaia, rich in nutrients such as vitamins, fibers, bioactive compounds, to produce various food products. The araucaria seed, known as pinhão, is also recognized for its richness in nutrients and functionality. It is a source of carbohydrates, dietary fibers, minerals and antioxidants, offering a healthy and ecologically sustainable alternative. Combining these ingredients to create a new food product enriches the diet, diversifies the diet, and values local resources, boosting economic progress in areas where they are found. In this context, this research was conducted to produce creamy sweets based on uvaia and guabiroba, enriched with araucaria seed flour, as a strategy for innovation and the valorization of native species. Three formulations were developed for each fruit, with different flour concentrations (0%, 5%, and 10%). Moisture, water activity (Aw), acidity, pH, soluble solids content, and rheological, colorimetric, and microbiological analyses were evaluated. The physicochemical analyses showed that the jams presented characteristics suitable for conservation, with low moisture, and acidity and pH, and high sugar concentration. The pH stability in the jams developed and the adequate Aw values indicate that adding pine nut flour does not compromise acidity and microbiological safety. Adding of pine nut flour results in a significant decrease in moisture and increases the percentage of ash (minerals). The analysis of the drying kinetics of cooked pine nuts at temperatures of 50, 70, and 90 ºC, revealed that the drying rate increases with increasing temperature and that cooked seeds dried faster than raw ones. The inclusion of flour changed the rheological properties of texture and viscosity of the sweets, making the products harder, more adhesive, cohesive, and gummier. On the other hand, they were characterized as thixotropic and pseudoplastic fluids whose behavior is predominantly elastic. It was observed that the addition of pine nut flour promoted small changes in the color parameters, especially in ΔE, which shows that the total magnitude of the color difference is noticeable, especially with 10% pine nut flour. Microbiological analyses indicate that the sweets were produced with good manufacturing practices for the microorganisms studied, ensuring food safety. Developing sweets from native fruits is a commercial and sustainable strategy that contributes to preserving biodiversity and economic development. Pine nut flour is a healthy and sustainable alternative, promoting health and the efficient use of natural resources.